Strategiczne i operacyjne zarządzanie kosztami w zakładzie ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (Strategic and Operational Cost Management in an Insurance Company, 2008)
Cost management is a very important part of management in each company, especially in insurance companies which should concentrate on reaching satisfying results. Management accounting is an information system which generates data base for cost management. This process contains such tasks as: finding out common elements for the chosen strategy of an insurance company and costs reduction, preparing the partition strategic tasks in three insurance company activity areas, selection and elaboration of proper cost accounting system, preparation costs budgeting, monitoring actions and operations, preparing costs calculation report according to received early costs classification, control and deviations analysis, estimation of cost management process application.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 16-23